Relationship of Initial Pancreatic Enzyme Replacement Therapy Dose With Weight Gain in Infants With Cystic Fibrosis. Issue 4 (October 2018) - Schechter, Michael S.; Michel, Suzanne; Liu, Shufang; Seo, B. Woun; Kapoor, Mudra; Khurmi, Rupal; Haupt, Mark
ABSTRACT: Objective: The aim of the study is to test the hypothesis of a positive relationship between initial dose of pancreatic enzyme replacement therapy (PERT) in infants with cystic fibrosis (CF) and optimal weight gain over the first 2 years of life. Methods: Using the CF Foundation Patient Registry, we identified 502 children born in 2010 and used multivariable models to compare as our primary analysis their 2-year changes in weight-for-age z score (WAZ) and as our secondary analysis weight-for-length percentile (W/L%) by initial PERT dose. We focused on initial dose without reference to subsequent changes in treatment to avoid confounding by indication (severity). Results: Initial PERT dose demonstrated a linear relationship to change in WAZ and W/L% at age 2 years. An initial dose of >1500 lipase units/kg/largest meal resulted in a higher likelihood of attaining WAZ at 2 years at or above the birth WAZ (adjusted odds ratio [aOR] 1.87, 95% confidence interval [CI] 1.22–2.86) and at the top quartile for improvement over 2 years in WAZ (aOR 1.90, 95% CI 1.19–3.05). There was no correlation between initial PERT dose and weight at initial PERT encounter ( P = 0.35). Findings were similar for W/L% and when the cohort was restricted to infants who began PERT in the first 3 months of life. Conclusions: Infants receiving higher initial PERT dose demonstrate better weight-related outcomes, as reflected by attainment of favorable changes in WAZ and W/L%, at age 2 years. Abstract : Supplemental Digital Content is available in the text